Strategi Pemberdayaan Masyarakat oleh YBM Brilian dalam Meningkatkan Kesejahteraan Masyarakat - Berlianti, Berlianti; Bangun, Yolanda Oktari Br; Maisaroh, Anita; Sipayung, Dwinata Novelia (Lembaga Yasin AlSys, 2025)
Community empowerment is the first step in achieving social welfare. One of the things that is done in an effort to improve social welfare is social security through social assistance provided by institutions, both government and non-government institutions. One of them is the Yayasan Baitul Maal Bank Rakyat Indonesia (YBM BRILIaN). YBM BRILIan is committed to providing social assistance as stated in the programs offered. In this case, YBM BRILIaN not only provides social assistance to the community, but also provides programs where the purpose of this program is an effort to empower the community to create an empowered community and can develop the potential that exists in the community. The strategies carried out reach various aspects of life, ranging from economics, education, health, preaching and social humanity.